2021
DOI: 10.1038/s41598-021-96580-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary forage to concentrate ratio on nutrient digestibility, ruminal fermentation and rumen bacterial composition in Angus cows

Abstract: This study evaluated effects of dietary forage to concentrate ratio (F:C) on the body weight, digestibility, ruminal fermentation and rumen bacterial composition in Angus cows. Three diets with different F:C (LCD: 65:35, MCD:50:50, and HCD: 35:65) were fed to ninety Angus cows (3.2 ± 0.18 years old, 387.2 ± 22.6 kg). The average daily gain (ADG) and ammonia nitrogen concentration increased (P = 0.039 and P = 0.026, respectively), whereas the acetate to propionate ratio (P = 0.027) and the neutral detergent fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 67 publications
(86 reference statements)
9
29
0
Order By: Relevance
“…Increasing the concentrate proportion increased ( p < 0.05) DM intake and digestibility of DM, OM, and CP but decreased ( p < 0.05) NDF and ADF digestibility. These findings agree with Chen et al [ 27 ], cow fed a high concentrate diet showed significantly increased digestibility of nutrients. It could be due to the concentrate diet can provide additional nutrients for rumen microbial growth and can enhance rumen fermentation.…”
Section: Resultssupporting
confidence: 93%
“…Increasing the concentrate proportion increased ( p < 0.05) DM intake and digestibility of DM, OM, and CP but decreased ( p < 0.05) NDF and ADF digestibility. These findings agree with Chen et al [ 27 ], cow fed a high concentrate diet showed significantly increased digestibility of nutrients. It could be due to the concentrate diet can provide additional nutrients for rumen microbial growth and can enhance rumen fermentation.…”
Section: Resultssupporting
confidence: 93%
“…Many studies have confirmed that the metabolism in the cecum of meat rabbits is similar to that in the rumen, and there are cocci similar to the rumen in the cecum of meat rabbits ( 34 ). Ruminococcaceae can degrade cellulose and hemicellulose in feed, produce butyrate by fermenting complex non-digestible polysaccharides, and plays a pivotal role in the maintenance of intestinal health ( 35 ). This study, may explain the significant increase of butyric acid content in AM- and PV-treated meat rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR conditions for amplifying the 16S rDNA gene are as follows: initial denaturation at 95°C for 1 min, followed by 27 cycles of denaturation at 95°C for 30 s, annealing at 55°C for 30 s, extension at 72°C for 45 s, and a final extension at 72°C for 10 min. The PCR products were detected using agarose gel electrophoresis (2% gel), purified using the AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA), and quantified using the Quantus™ Fluorometer (Promega, USA) ( Chen et al., 2021 ). The purified amplicons were sequenced using the Illumina MiSeq PE300/NovaSeq PE250 platform (Illumina, San Diego, CA, USA), according to the standard protocol of Meggie Biological Co., Ltd. (Shanghai, China) ( Chen et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR products were detected using agarose gel electrophoresis (2% gel), purified using the AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA), and quantified using the Quantus™ Fluorometer (Promega, USA) ( Chen et al., 2021 ). The purified amplicons were sequenced using the Illumina MiSeq PE300/NovaSeq PE250 platform (Illumina, San Diego, CA, USA), according to the standard protocol of Meggie Biological Co., Ltd. (Shanghai, China) ( Chen et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%